Magnetic Properties of Rf Magnetron Sputtered Co-Ag-Cu Granular Thin Films - Kabashi, Kabashi Khatir (2000)
The observation of the magnetoresistance (MR) effect in granular films, where the magnetic particles are embedded in a non-magnetic matrix, has stimulated remarkable interest because of its potential technological application as magnetic sensors in the magnetic storage technology, and also due to interest in fundamental scientific research . The granular films can present MR effect even larger than in multilayers The MR effect was a large decrease in electrical resistivity that occurs when the magnetization of two layered or granular samples was aligned by an external magnetic field. In surface morphology was smooth and homogeneous and there was a little contamination on these surfaces as indicated through SEM, which may be attributed to the oil spots and fingerprints throughout the deposition process and preparation for various measurements. The chemical composition and the element percentage for each series were determined by ED X The structure of the samples was characterized by XRD. The peaks of fcc (III), (200), (220), and (311) related to the Ag were detected and a set of fcc (III) and (220) peaks related to the Co were defected as well, indicating the formation of small fccCo particles in Ag The XRD measurements also detected the peak of fcc (III) related to the Cu and Co. However, the other peaks of fccCu (+Co) (200) and fcceu (+Co) (220) were not detected Ag (III) peak shifts to higher angles (28 > 38 II) for the samples of Coo 53Ago 47, Coo 23Cuo 77, and Coo 32AgO.14CUO 54, while for the Coo 2 6AgO. 19CUO.55 and Coo 3oAgo 4 6CUO.24 samples the peak shifts to lower angles (28<38.11). The as-deposited samples measurements at room temperature displayed a maximum value of 1.26% MR obtained by the Coo 32AgO .1 4CUO 54 film when the deposition time was 80 minutes. The remaining samples of Coo 23CUO 77, Co o ZGAgo 19CUO 55, Coo 30Ago 4GCUo 24, and Coo 55Ago 47 have shown the values of 0.13%, 0.24%, 0.36%, and 0.84% MR respectively for the deposition time of 90 minutes. Post-annealing increased the MR for all the samples at room temperature and at low temperatures. The measurements of annealed samples at room temperature exhibited the values of 1.75%, 1.28%, 0.52%, 0.31%, and 0.Coo J2Ago 14CUO.54, Coo 53Ago 47, Coo 30AgO AGCUO 24, Coo 2 6Ago 19CUO 55, and Coo 23CU 0.77 respectively of the samples deposited for 90 minutes. The increase in the MR due to annealing process may be related to the reducing of the degree of structural disorder, enlarging the particle size and increasing of the interparticle separation, which may affect to the effect of phonon behavior on the resistivity of the film.